Comparative legal study on the regulation of medicine advertisement in Malaysia and Australia / Ahmad Zuhri Md Ali - Md Ali, Ahmad Zuhri (2018)
Advertisement can be a source of information for the viewers to understand and appreciate the product being marketed. Same goes to advertisement of medicine and medicinal products. Consumers may gain some knowledge through advertisement and making them able to make inform decisions in purchasing medicine for the treatment of their illnesses or in maintaining their general health. However, to achieve this objective, advertiser must also be a responsible party. A truthful, fair, ethical, accurate and balance information and claims in an advertisement will definitely benefits the viewers and consumers. In ensuring this system works well, a proper and extensive controls is needed. Whether through legal frameworks or effective administrative measures, this aim could only be achieved if it is done in proper manner and efficiently. The current legal frameworks in Malaysia may have some flaws and shortcomings. This research intends to explore these issues. With that findings, further recommendations could be made for the regulators and legislators to deliberate about. In doing so, there is nothing wrong for us to look around on what other countries are doing and how does they manage medicine advertisement in their country. Australia being a well-developed nation and inheriting the same common law system like in Malaysia, is chosen in this study. Australia’s law on medicine advertising is explored and understood. In the end, this study will bring forward certain issues that require quick corrections while at the same time suggesting some applicable measures or concept done by Australia to be applied locally, either in term of legal frameworks or non-legal approaches of medicine advertisement control. Ultimately, the whole purpose of this study and the control of medicine advertisement in general, is for the benefits of the public health which in turn, would give impact to the nation as a whole, either economically or in their social behavior.